Clinical characteristics and outcomes of children admitted to adult intensive care and high-dependency units in Kenya: a multicenter registry-based analysis - Mwangi, Wambui; Njoki, Carolyne; Kaddu, Ronnie; Simiyu, Nabukwangwa; Sulemanji, Demet; Oduor, Peter; Dona, Dilanthi Gamage; Abonyo, Teddy Thaddeus; Wangeci, Patricia; Kabanya, Thomas; Mutuku, Selina; Kioko, Annastacia; et al. (Frontiers in Pediatrics, 2025)
ProblemThere is limited information on the prevalence, clinical features and outcomes of pediatric patients admitted to adult intensive care units (ICUs) or high-dependency units (HDUs) in low and middle income countries (LMICs).ObjectiveTo evaluate the clinical characteristics and outcomes of critically ill children admitted to adult ICU or HDU in Kenya.MethodsWe conducted a registry–enabled study leveraging on data collected progressively in the Kenya Critical Care Registry comprising six ICUs and five HDUs. We included all consecutive encounters of patients younger than 18 years who were admitted to the study units from January 2021 to June 2022.OutcomesThe primary outcome was ICU or HDU mortality; secondary outcomes included clinical management, duration of invasive ventilation, length of stay in the ICU or HDU and risk factors for mortality.ResultsOf the 5012 ICU and HDU admissions, 466 (9.1%) were patients younger than 18 years. Their median age was 2.0 [0.4–9.0] years, with 173 (37.1%) children being under one year. Medical admissions accounted for 357 (76.6%) cases, while 109 (23.9%) were surgical. Almost half of the children received invasive ventilation, whereas noninvasive ventilation was rarely used. The use of cardiovascular support and renal replacement therapy was also uncommon. Approximately one quarter of children were sedated on admission, and more than 80% received at least one antibiotic. The overall ICU or HDU mortality rate was 34.5%, higher in medical cases than in surgical cases (39.5 vs. 18.3%, p < 0.001). Independent risk factors for mortality were age under 28 days, admission due to a medical reason and receiving invasive ventilation.ConclusionsIn a representative sample of Kenyan ICUs, one out of nine admissions to adult ICUs and HDUs involves a child, who often receive invasive ventilation and have a high crude mortality rate. In this cohort of patients, all risk factors for mortality were non-modifiable.